The richness of CONNEX research in a nutshell - Kohler-Koch, Beate (2008)
Abstract: "In order to do justice to the complexity of EU governance, research was organised in six Research Groups each approaching the 'problematique' of efficient and democratic multi-level governance from a different perspective. Researchers addressed the institutional architecture of the EU system as well as the nature and effects of old and new instruments of governance. They put the ways and means of enhancing democracy in the EU system under scrutiny and examined the gains and challenges of civil society participation. By bringing together a multi-disciplinary and multi-national group of scholars the diversity of approaches came to the fore and added to a highly differentiated picture of the European governance system. The productivity of CONNEX is manifest in an impressive publication output. The richness of research findings is visible in the summary reports of the individual Research Groups which are documented in the second part of this chapter." (excerpt)